Neutron radiography and numerical simulation of mixing behavior in a reactor for supercritical hydrothermal synthesis. Issue 3 (29th December 2013) - Sugioka, Ken‐ichi; Ozawa, Kyohei; Tsukada, Takao; Takami, Seiichi; Adschiri, Tadafumi; Sugimoto, Katsumi; Takenaka, Nobuyuki; Saito, Yasushi
<x xml:space="preserve">Abstract</x> We have visualized the distributions of temperature and water density in a tubular flow reactor for supercritical hydrothermal synthesis of nanoparticles by neutron radiography, and investigated the effect of reactor configuration on the mixing behavior in the reactor. Here, three types of reactors were used, and the mixing behaviors of supercritical water and room‐temperature water at a T‐junction in the reactors were observed. As a result, it was revealed that the distributions of temperature and water density in the tubular flow reactors strongly depend on their configurations by neutron radiography. In addition, numerical simulations have been carried out to investigate the flow patterns and temperature distributions in the reactor in detail using the commercial software FLUENT, and it was demonstrated that the numerical results can explain the experimental results obtained by neutron radiography well. © 2013 American Institute of Chemical Engineers AIChE J, 60: 1168–1175, 2014